The relationship between schizotypal personality features and mind wandering among college students during COVID-19 pandemic: A moderator of depression - Guojun Zhao; Guojun Zhao; Shuangchen Li; Qi Zhang; Xiaoxiao Guo; Fusen Xie; Shuhong Yan; Haijian Liu; Yuan Chong; Yuee Ding; Xu Li (Frontiers in Psychiatry, 2023)
IntroductionAlthough the impact of the COVID-19 pandemic on people’s mental health has been well documented in many studies, the schizotypal personality features in the general population have not received sufficient attention.MethodsStudy 1 is a longitudinal study tracking changes in schizotypal personality features among college students during the COVID-19 pandemic. A total of 153 Chinese college students were assessed using the Schizotypal Personality Questionnaire. Study 2 explored the relationship between schizotypal personality features, mind wandering, and depression. A total of 557 college students completed the Schizotypal Personality Questionnaire, the Beck Depression Inventory, and the Mind-Wandering Questionnaire during the COVID-19 pandemic.ResultsStudy 1 results showed that the scores from later stages in the pandemic were significantly higher than those from the initial stages on each dimension of schizotypal personality, which means that the schizotypal personality features became more obvious during the COVID-19 pandemic. Study 2 results showed that there was a positive correlation between schizotypal personality features, depression, and mind wandering.DiscussionDepression played a moderating role in the relationship between schizotypal personality features and mind wandering. The schizotypal personality features of college students increase during COVID-19; it has a positive relationship with mind wandering; depression moderates the relationship. We discussed these findings and provided some suggestions about future research.